The diminishing divide : religion's changing role in American politics - Kohut, Andrew (Book collections on Project MUSE., 2000)
"Drawing on extensive survey data from the Pew Research Center, the National Election Studies, and other sources, The Diminishing Divide illuminates the historical relationship between religion and politics in the United States and explores the ways in which religion will continue to alter the political landscape in the century before us. A historical overview of religion in U.S. politics sets the tone as the book examines the patchwork quilt of American religion and the changing role of religious institutions in American political life since the 1960s. The book explores the complex relations between religion and political attitudes, as well as that of religion and political behavior - particularly with respect to party affiliation and voting habits.